KONSEP NASAKH MAHMUD MUHAMMAD THAHA DAN IMPLIKASI TERHADAP HUKUM ISLAM - Kholidah, Kholidah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
The concept of nasakh be the gateway for Mahmoud Muhammad Thaha, to perform evolution syari’ah. Displacement texts Madaniyah to the texts Makkiyah a certainty, that Islamic law capable to solve the problems internasional and also human righat carried by kolonialis England in Sudan. The texts Makkiyah is universal, substantive, protective the all mankind, equal and democratic. Whereas texts Madaniyah becomes established Islam and protected the internal ummah with locally and temporarily additional rules. Some additional rules are not derived from the original sources of Islam, the Qur’an and hadith. Therefore, according to Thaha, Islamic law needs to be reformed in order to adjust it to the demands of modern time so that Islamic law play sicnificant role in the formation of humanist and democratic world.